Makmeugang Tradition in Acehnese Society - Nasution, Abdul Gani Jamora; Siregar, Aviva Hanum; Khairunnisa, Sabina; Ridwan, Fitri Syakira (Yayasan Pendidikan Islam Akmalia, 2023)
The purpose of this study is to find out how the meugang tradition in Acehnese society is. The method used in this research is a qualitative descriptive method. The research results obtained are that the Maugang tradition is a tradition originating from Aceh which is still carried out today. This tradition is carried out by slaughtering livestock which will then be distributed to people in need, this aims to strengthen friendship and at the same time give alms. Usually this tradition is carried out as a form of gratitude to welcome holidays, such as fasting in Ramadan, Eid al-Fitr and Eid al-Adha